Escherichia coli isolates from domestic poultry - MISHRA, ARCHANA; SHARDA, RAKESH; CHHABRA, DAUEET; MOGHE, M. N (The Indian Journal of Animal Sciences, 2014)
Strains (50) of Escherichia coli were isolated from 250 clinical specimens collected from poultry birds: majority of these were recovered from heart blood. Biochemical characterisation revealed 48.0 and 16.0% atypical strains producing H2S and urease respectively. Isolates (43) were typed into 17 different ’O’ serotypes; 078 was the predominant. The other serogroups isolated in decreasing frequency were O2,O19,O20, O90,O38, 0109,O81,O148, O162,08,016,O60, O63, O68, O139 and O152, some of which are of zoonotic significance. Six strains remained untypable and 1 was rough. All the isolates were Congo-red (CR)-positiveÂ and 15 produced haemolysis on sheep blood agar. Whole bacterial culture of 45 strains and cell free flitrates of all the isolates caused mortality in mice and chicken embryos. Serotypes 08 and 078 produced enterotoxin in the ligated rabbit ileal loops. A polyvalent adjuvanted vaccine was prepared and found immunogenic.